AKSESIBILITAS DAN EFEKTIVITAS PEMBELAJARAN DARING DI STKIP PGRI BANGKALAN PADA MASA PANDEMI COVID-19 - Hefi Rusnita Dewi; Abdur Rosyid (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aimed to determine the accessibility and effectiveness of online learning in the active participation of STKIP PGRI Bangkalan students in the Bangkalan region. This research is a type of quantitative descriptive research conducted by distributing questionnaires to STKIP PGRI Bangkalan students who live in the Kokop, Geger, and Galis Bangkalan areas during the Covid-19 pandemic and then tabulating data to calculate the percentage of students' active participation in online learning using various applications and barriers to online learning. Summary of the results of a student survey on the accessibility and effectiveness of online learning during the Covid-19 pandemic based on a preliminary study, in which around 86.6% of respondents stated that it was difficult for internet signals to attend lectures via Zoom and Moodle while learning with the help of the WA Group allowed 100% of students to participate actively. Based on the current survey results, the biggest obstacle to online learning for students is the difficulty of accepting the Internet at their residences.